Some examples of Croatian dialects' influence on the lexical diversity of the contemporary linguistic idiom of Zadar among non-native elderly speakers - Vrsaljko, Slavica (Array, 2019)
The synchronic linguistic situation of the urban idiom in the city of Zadar is a result of several strands of dialectal influence: Neo-Shtokavian dialect spoken in the hinterland, Chakavian ikavian (“ikavski”) idiom spoken in the coastal region of Croatia, Central Chakavian ikavian-ekavian (“ikavski-ekavski”) dialect and standard Croatian. Lisac established that the contemporary Zadar idiom consists of a mixture of two Croatian dialects, Chakavian and Shtokavian, each in turn further subdivided into Central Chakavian and South Chakavian, Bosnian-Herzegovinian and East Herzegovinian, respectively. Due to varied historical circumstances, within these dialects we find a number of loanwords, mostly Turkish in Shtokavian and Romance borrowings in the Chakavian dialect. To this end the paper uses linguistic contact theory, applied in research on dialects, and explores influence in one direction only: it explores the presence of Turkish loanwords in Croatian idiom of Zadar (in its Shtokavian dialectal component) and Romance loanwords in the Zadar idiom (in its Chakavian component) but not the influence of Croatian on either Turkish or Romance languages. Hence the recipient language is Croatian (here specifically its Zadar idiom) while the donor languages are Turkish and Romance languages, mainly Venetian Italian but also standard Italian, and in some cases we are dealing with linguistic relics of Romance Dalmatian language in Croatian. We have selected to analyse Turkish loanwords in the Shtokavian dialect and Romance loanwords in the Chakavian dialect (within the Zadar idiom) because they are the most frequent foreign borrowings in the Zadar idiom, especially Romance elements that pervade the varieties of Croatian spoken in the coastal region (they often remain on a regional level only but some have passed from Chakavian into Croatian standard).